Modeling of alkynes: synthesis and theoretical properties - Rosseto,Renato (2003)
In this paper we present the synthesis and simulation of alkynes derivatives. Semiempirical calculations were carried out for the ground and first excited states, including the spectroscopic properties of the absorption and emission (fluorescence and phosphorescence) spectra by INDO/S-CI and DNdM-INDO/S-CI methods with geometries fully optimized by PM3/CI. The fact that the theoretical spectra are in accord with the experimental absorption spectra gives us a new possible approach on how structure modifications could affect the non-linear optical properties of alkynes.